ナンキョクカイ ライギョダマシ ギョニク ノ シシツ ブンセキ - 大野, 佳美; オオノ, ヨシミ; 矢野, 郁也; ヤノ, イクヤ; 和栗, 修; ワグリ, オサム; OHNO, Yoshimi; YANO, Ikuya; WAGURI, Osamu (国立極地研究所, 1976)
P(論文) 南極産ライギョダマシ(Dissostichus mawsoni NORMAN)骨格筋の脂質ならびに脂肪酸分析を行い,次の結果を得た.中性脂質は総脂質の98%を占めたが,リン脂質はわずか2%,またはそれ以下であることが薄層クロマトグラフィー,およびカラムクロマトグラフィー分析により明らかとなった.直接ガスクロマトグラフィーによって,トリグリセリドの主要分子種はC_<44>,C_<46>,C_<48>,C_<50>,C_<52>およびC_<54>であり,その脂肪酸組成は他の海産魚油中のものと類似しており,主要成分はC_<16:0>,C_<18:0>,C_<16:1>,C_<18:1>,C_<18:2>,C_<20:5>およびC_<22:6>で,少量ながらC_<20:1>,C_<22:1>およびC_<24:1>が含まれていた.また,グリセリドにおける脂肪酸の位置特異性をリパーゼ,およびホスホリパーゼA_2を用いてしらべたところ,1位には飽和およびモノエン脂肪酸が結合し,2位には多不飽和脂肪酸が多く結合していた. Lipid and fatty acid composition of skeletal muscle of antarctic giant fish (Dissostichus mawsoni NORMAN) were examined. Thin-layer and column chromatography showed that the neutral lipids made up 98% of the total lipids, while phospholipids only 2% or less. The direct gas chromatographic analysis of triglycerides revealed that the major molecular species were C_<44>, C_<46>, C_<48>, C_<50>, C_<52> and C_<54>, that their fatty acid composition resembled the other edible oil of marine fishes, and that the major components were C_<16 : 0>, C_<18 : 0>, C_<16 : 1>, C_<18 : 1>, C_<18 : 2>, C_<20 : 5> and C_<22 : 6> with smaller amounts of C_<20 : 1>, C_<22 : 1> and C_<24 : 1>. The positional distributions of fatty acid on glycerides was also determined by lipase and phospholipase A_2 treatment and it showed that saturated and monoenoic fatty acids occurred in 1 position, while polyunsaturated fatty acids in 2 position, exclusively. departmental bulletin paper